Interpretation of Basic and Advanced Urodynamics - Firoozi, Farzeen; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides a comprehensive, state-of-the-art review of this evaluation of voiding disorders and will serve as a valuable resource for clinicians and surgeons. The book reviews the basic indications for urodynamics as well as the interpretation of basic and advanced studies with the use of clinical vignettes. In addition to step-by-step description in text, the textbook provides illustrations/photographs and tracings of different urodynamics scenarios. This atlas of urodynamics will serve as an extremely useful resource for physicians dealing with and interested in the evaluation of pelvic floor disorders and voiding dysfunction. It will provide a concise and comprehensive review of all the different types of urodynamics scenarios, while instructing its readers on how to accurately and consistently interpret these studies. All chapters are written by experts in the fields of pelvic floor disorders and voiding dysfunction.
Equipment, Setup, and Troubleshooting -- Terminology -- Overactive Bladder: Idiopathic -- Overactive Bladder: Neurogenic -- Stress Urinary Incontinence: Female -- Stress Urinary Incontinence: Male -- Bladder Outlet Obstruction: Male Non-neurogenic -- Bladder Outlet Obstruction: Female Non-neurogenic -- Bladder Outlet Obstruction: Neurogenic -- Post-Outlet Intervention for BOO: Female -- Post-Outlet Intervention for BOO: Male -- Post-Outlet Intervention for SUI: Female -- Post-Outlet Intervention for SUI: Male -- Bladder and Urethral Anatomic Anomalies -- Pelvic Organ Prolapse -- Post-Reconstruction for Pelvic Organ Prolapse -- Urinary Diversion/Augmented Lower Urinary Tract -- Adolescent/Early Adulthood Former Pediatric Neurogenics: Special Considerations.
Keywords: Medicine; Gynecology; Urology; Medicine & Public Health; Urology; Gynecology